Valences of historiography
1 online resource (xi, 144 pages)
Keywords: "The compiled essays offer various themes and ways of approaching historiography. Each chapter probes the state of contemporary theorization of architecture histories, working toward the theme of critical re-writing of history. Essential to each author's contribution is specific traditions created by the mole of history burrowing through the past. This book concerns the historian's conjectures towards capturing the past and present zeitgeist. Temporality is the theme running through the narrative of this volume. It raises the question if the ever-growing body of work on architectural history should be taken for history as such. More specifically, what is the intersection between history and architecture history? Furthermore, whether every text focused on architecture's past categorically historiographic? Still, in what capacity does architecture history indexes history beyond contingencies and without reducing the text to empirical realities and the historian's interest in a specific subject, including those collected through archival research, itself an emblem of textuality? This book upholds the conviction that the past should be recalled accurately and that there is no history but historical criticism, the scope of which exceeds the historicity of Humanism. Dialectically, the timeline experienced across contemporary techno-economic and cultural domains (aesthetics) offer an opportunity to explore architecture produced outside the Euro-American continents. Valences of Historiography offers a fresh take on architectural history that is useful for academics, researchers, and architecture students"--